A6.6 Functional pathways in endothelial cells are differentially regulated by fibroblasts from patients with RA and resolving disease. (13th February 2015) - McGettrick, HM; Naame, N; He, S; Raza, K; Nash, GB; Buckley, CD; Filer, A
Abstract : Objectives: Fibroblasts have been shown to actively regulate the inflammatory infiltrate that accumulates within synovial joints. On way they achieve their effects in part by conversing with neighbouring vascular endothelial cells imparting a stromal "address code" that regulates leukocyte recruitment. Here we compared the ability of synovial fibroblasts from resolving arthritis and very early RA to communicate with vascular endothelial cells (EC). Methods: Fibroblasts were isolated from synovial biopsies taken from treatment naive patients with a new onset of clinically apparent arthritis and symptom duration of ≤12weeks, who at follow-up had either a resolving arthritis or RA (VeRA). Endothelial cell-fibroblast co-cultures were formed using porous filters for 24 h prior to a further 24 h stimulation with tumour necrosis factor alpha and interferon gamma. Microarray analysis was performed on mRNA extracted from endothelial cells and evaluated using Ingenuity Pathway Analysis. Results: Resolving and VeRA fibroblasts differentially modified the transcriptional profile of EC. There were 52 differentially expressed genes (76 probe sets) between the two conditions, with 21 genes expressed higher in EC from VeRA co-cultures compared to resolving co-cultures. These related to 18 ingenuity canonical pathways associated with cell signalling (e.g. Wnt and NKFB pathways), cellular differentiation, and metabolism (e.g. lipid and amino acid). Conclusions: Fibroblasts from acutely resolving and early persistent arthritis are distinct. Differences in the way in which fibroblasts communicate with endothelial cells could be involved in the pathogenesis and perpetuation of the inflammatory response in the earliest clinically apparent phases of RA.